The Effect of Free Cash Flow and Corporate Governance on Earnings Management: The Moderating Role of Stock Liquidity - Joanna; Mardianto (Universitas Nahdlatul Ulama Surabaya, 2025)
This study examines the influence of free cash flow and corporate governance index (CGI) on both accrual and real earnings management practices, with a focus on the moderating role of stock liquidity. Using a quantitative approach, this research analyzes data listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. A sample of 90 companies with 450 company-year observations was used, which were then analyzed using balanced panel regression. The results show that free cash flow has a significant positive effect on accrual earnings management and a negative effect on real earnings management. CGI, stock liquidity, as well as the moderating role of stock liquidity on the relationship between CGI, were found to have no significant effect on earnings management.